Reflections on patient safety incident reporting systems - Maria de Jesus Castro Sousa Harada; Ana Elisa Bauer de Camargo Silva; Liliane Bauer Feldman; Sheilla Siedler Tavares; Luiza Maria Gerhardt; Antônio José de Lima Júnior; Adriane Cristina Bernat Kolankiewicz (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To reflect on the main characteristics and recommendations of Incident Reporting Systems, discuss the population's participation in reporting, and point out challenges in the Brazilian system. Method: Reflection study, based on Ordinance No. 529/13, which instituted the National Patient Safety Program, under Collegiate Board Resolution (CBR) No. 36/13; reflections by experts were added. Results: Reporting systems are a source for learning and monitoring, allow early detection of incidents, investigations and, mainly, the generation of recommendations prior to recurrences, in addition to raising information for patients and relatives. There is little participation of the population in the reporting, regardless of the type of system and characteristics such as confidentiality, anonymity, and mandatory nature. Final Considerations: In Brazil, although reporting is mandatory, there is an urgency to advance the involvement and participation of the population, professionals, and institutions. To simplify data entry by improving the interface and importing data from the reporting system is an objective to be achieved.